S-Methadone augments R-methadone induced respiratory depression in the neonatal guinea pig - Silverman, Daniel A. N. (2009)
Methadone is administered as a racemic mixture, although its analgesic and respiratory effects are attributed to R-isomer activity at the mu-opioid receptor (MOP). Recently, we observed a four-fold increase in inspiratory time in three-day old guinea pigs following an injection of racemic methadone. We hypothesized that this effect was due to augmentation of R-methadone induced respiratory depression by the S-methadone isomer. In the current longitudinal study, we injected three-, seven-, and fourteen-day old neonatal guinea pigs with saline, R-methadone, S-methadone, or R- plus S-methadone in order to characterize the roles of the individual isomers, as well as the synergistic effects of co-administration. Using plethysmography, we measured respiratory parameters while breathing room air and during a 5% CO(2) challenge. S-methadone alone had no respiratory effects. However, the R- plus S-methadone group showed greater respiratory depression and increased inspiratory time than the R-methadone group in the youngest animals, suggesting that the respiratory effects of R-methadone are augmented by S-methadone in early development.